PELATIHAN ETIKA BERMEDIA SOSIAL BERBASIS NILAI PANCASILA UNTUK SISWA SEKOLAH DASAR DI BANDAR LAMPUNG - Halim, Abdul; Febra Anjar Kusuma; Susilo; Karyadi Hidayat; Fitra Endi Fermanda; Teki Prasetyo Sulaksono; Herbiyansa Putra Pratama; Ari Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid use of social media among elementary school students has increased the risk of digital ethical issues, such as cyberbullying, misinformation, and inappropriate online communication. This community service article aims to develop and implement a social media ethics training model based on Pancasila values, integrated with digital citizenship and critical media literacy within the elementary school environment. The program was designed using a participatory approach through a series of activities, including interactive counseling, workshops, case-based discussions, simulations of ethical digital behavior, and teacher mentoring supported by systematic practical guide modules. The effectiveness of the program was evaluated using a mixed-method approach, combining pretest and posttest assessments to measure participants’ understanding, along with observations of behavioral changes and participant reflections throughout the activities. The qualitative findings indicate an improvement in students’ awareness of polite online communication, increased caution in filtering and sharing information, and the development of tolerance in responding to differing opinions. The integration of Pancasila values serves as a contextual ethical foundation that strengthens the internalization of responsible digital behavior, thereby contributing to the development of adaptive and integrity-driven student character in the digital era.